â€œPLACE ATTACHMENTâ€ PEMUKIM PASCARELOKASI DI KOTA PALU - Batudoka, Zubair (MEKTEK, 2005)
The limited of land and accesibility of the low income people in Palu city caused the growth of illegal informal settlements. Within its settlement development programs, the local government of Palu was applying a relocation policy. Relocation of the informal coast settlement for Besusu Barat and Talise district to Layana Indah in North Palu. After the relocation (pascarelokasi) some of dwellers behave the resisting, some of other hold out at settlement after the relocation. This condition showed the â€œplace attachmentâ€. Research to " place attachment"Â  the settlement after relocation conducted a qualitative, through phenomenologic approach with symbolic interaction model. In order to validate the research, the researcher used qualitative approach with causal method. Analitic narative and statistical description were used for analizing the data.The result of research indicate that the place attachment of settler after relocation enable the happening of 'dilution' and also ' reinforcement' binding to its dwelling. In the end will give the mental picture about the ideal dwelling. Attached of settler before relocation compared by related after relocation especially with the physical aspect of concerning settlements condition and the non physical specially pursuing of its settler economics mobility